Integration without joining? Neighbourhood relations at the Finnish - Russian border - Anaïs Marin (Danish Institute for International Studies (DIIS), 2006)
The Finnish-Russian border is one of the oldest dividing lines on the European continent, but also the most stable and peaceful new border the EU has been sharing with Russia since 1995. After the fall of the Iron Curtain, it became both a site and an instrument of increased crossborder interaction and institutional innovation, as illustrated by the establishment of Euregio Karelia in 2000. The paper recalls the historical background of good-neighbourhood in the Finnish-Russian/Soviet borderlands and calls on constructivist IR theory to elaborate a model for analysing the factors, actors and mechanisms that contributed to the partial integration of this frontier. With Russian regions adjacent to the EU/Finnish border participating in the Northern Dimension, cross-border cooperation contributed to the growing regionalisation of the EU-Russia “strategic partnership”. The paper addresses the challenging conceptual and political issues posed by this trend towards an “integration without joining” at the EU's external border.
Keywords: 330; Grenze; Grenzgebiet; EU-Regionalpolitik; Politische Integration; Finnland; Russland; Karelien